Application of Machine Learning Algorithms in Plant Breeding: Predicting Yield From Hyperspectral Reflectance in Soybean - Yoosefzadeh-Najafabadi, Mohsen; Earl, Hugh J.; Tulpan, Dan; Sulik, John; Eskandari, Milad (Frontiers in Plant Science, 2021)
Recent substantial advances in high-throughput field phenotyping have provided plant breeders with affordable and efficient tools for evaluating a large number of genotypes for important agronomic traits at early growth stages. Nevertheless, the implementation of large datasets generated by high-throughput phenotyping tools such as hyperspectral reflectance in cultivar development programs is still challenging, due to the essential need for intensive knowledge in computational and statistical analyses. In this study, the robustness of three common machine learning (ML) algorithms, Multilayer Perceptron (MLP), Support Vector Machine (SVM), and Random Forest (RF), were evaluated for predicting soybean (Glycine max) seed yield using hyperspectral reflectance. For this aim, hyperspectral reflectance data for the whole spectra ranged from 395 to 1005 nm, were collected at the R4 and R5 growth stages on 250 soybean genotypes grown in four environments. The Recursive Feature Elimination (RFE) approach was performed to reduce the dimensionality of the hyperspectral reflectance data and select variables with the largest importance values. The results indicated that R5 is more informative stage for measuring hyperspectral reflectance to predict seed yields. By considering either full or selected variables as the input variables, the ML algorithms were evaluated individually and combined-version using the Ensemble-Stacking (E-S) method to predict the soybean yield. Among all the individual tested algorithms, the highest Matthews Correlation Coefficient (MCC) and F-Measure were achieved in the RF algorithm with a value of 0.84 and 0.87, respectively. Therefore, by selecting RF as the metaClassifier for E-S method, the prediction accuracy increased to 0.93, using all variables, and 0.87, using selected variables showing the success of using E-S as one of the ensemble techniques. This study demonstrated that soybean breeders could implement E-S algorithm using either the full or selected spectra reflectance to select the high-yielding soybean genotypes, among a large number of genotypes, at early growth stages.